ANALYSIS OF INCREASING CUSTOMER SATISFACTION WITH LEO'S BAKSO IN MASTRIP, JEMBER DISTRICT WITH THE VARIABLES OF SERVICE QUALITY, PRODUCT QUALITY AND LOCATION - Yuniar, Etma Klisa; Rahayu, Jekti; Izzuddin, Ahmad (Dynamic Management Journal, 2024)
This study aims to find out and analyse the influence of Service Quality, Product Quality and Location on customer satisfaction of Leo meatballs in Jember City. The data used in this study is in the form of primary data obtained through the distribution of questionnaires, interviews and observations and the use of secondary data through documentation. The population in this study is Leo Mastrip meatball consumers, while the sample size of 102 respondents using accidental sampling to Leo meatball consumers who are purchasing products. xFor dataxanalysis, the authors used multiple linear regression analysis. Based on the results of hypothesis testing, it can be stated that ServicexQuality has a significant effect on Leo Mastrip Meatball Customer Satisfaction, Product Quality has a significant effect on Leo Mastrip Meatball Customer Satisfaction, and Location has a significant effect on Leo Mastrip Meatball Customer Satisfaction, as well as simultaneously Service Quality, xProduct Quality, andxLocation havexa simultaneous impact on Customer Satisfaction.